The City Lights and Christmas Spirit: On the Social Production of Festive Space (Seminar_BG, 2025)
The polemics surrounding the outdoor Christmas decoration of Sofia at the end of last year placed in the focus of public attention the role of urban design, urban decoration in particular, not only for the shaping of the city’s visual environment but also for the production of festive space. Inspired by Ivaylo Ditchev’s reflections on the city as a stage and the holiday as a media, this case study examines the tensions and conflicts emerging in the process of social production of festive space, brought about by a variety of factors and considerations – aesthetical, political, financial, environmental, commercial, and others – and seeks the projections of these conflicts in the virtual space of the social media, as that is where they have received the widest publicity. The analysis calls into question the initial research hypothesis that the city’s outdoor Christmas decoration is implicated in the political battles for urban space as public space, in other words – for the “right to the city”.  References:Dehaene, Michiel and Lieven De Cauter. 2008. “Heterotopia in a postcivil society”. In: Dehaene, Michiel and Lieven De Cauter (eds.). Heterotopia and the City. Public Space in a Postcivil Society. London and New York: Routledge, 3–9.Dichev, Ivaylo. 2005. Prostranstva na zhelanieto, zhelania za prostranstvo. Etyudi po gradska antropologia. Sofia: „Iztok – Zapad“.Dichev, Ivaylo. 2014. „Gradat kato protestna media“. Seminar_BG, 10B (https://www.seminar-bg.eu/spisanie-seminar-bg/broy10b/601-gradat-kato-protestna-media.html, last seen 12.12.2024 г.).Dichev, Ivaylo. 2018. „Praznikat kato media“. Balgarska etnologia/Bulgarian Ethnology/Ethnologia Bulgarica, 2, 167–177.Harvey, David. 2008. “The right to the city”. New Left Review, 53, 23–40.Harvey, David. 2012. Rebel Cities. From the Right to the City to the Urban Revolution. London and New York: Verso.Jalonen, Harri. 2014. “Social media – an arena for venting negative emotions”. Online Journal of Communication and Media Technologies, 4, 53–70. DOI: 10.30935/ojcmt/5704.Larsen, Timothy (ed.). 2020. The Oxford Handbook of Christmas. Oxford: Oxford UniversityPress.Lefebvre, Henri. 1968. Le Droit à la ville. Paris: Éditions Anthropos.Miller, Daniel (ed.). 1993. Unwrapping Christmas. Oxford: Clarendon Press.Miller, Daniel. 2017. “Christmas: An anthropological lens”. HAU: Journal of EthnographicTheory, 7(3), 409–442.Nissenbaum, Stephen. 1997. The Battle for Christmas: A Cultural History of America’s Most Cherished Holiday. New York: Alfred A. Knopf.van Bavel, Jay, Claire Robertson, Kareena del Rosario, Jesper Rasmussen and Steve Rathje. 2024. “Social media and morality”. Annual Review of Psychology, 75, 311–340.Waits, William. 1993. The Modern Christmas in America: A Cultural History of Gift Giving. New York and London: New York University Press.Whiteley, Sheila (ed.). 2008. Christmas, Ideology and Popular Culture. Edinburgh: EdinburghUniversity Press.Yanchev, Pavel. 2014. „Epizodi na urbanistichen aktivizam v Sofia – gradskite publichni prostranstva mezhdu institutsii i grazhdani“. Seminar_BG, 10B (https://www.seminar-bg.eu/spisanie-seminar-bg/broy10b/607-epizodi-na-urbanistichenaktivizam-v-sofia.html, last seen 12.12.2024 г.).
Keywords: outdoor Christmas decoration; urban design; festive space; public space; right to the city